2010
DOI: 10.1007/s10661-010-1445-0
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of some heavy metals in Hysterothylacium aduncum (Nematoda) and its host sea bream, Sparus aurata (Sparidae) from North-Eastern Mediterranean Sea (Iskenderun Bay)

Abstract: The sea bream's nematode and Sparus aurata, sampled from the Iskenderun Bay, Mediterranean, in March 2008 were analyzed by inductively coupled plasma-atomic emission spectrometry for their some heavy metal (Cd, Cr, Cu, Fe, Hg, Mn, Mg, Pb, and Zn) levels. The metal concentrations of the parasites were compared to different organs (liver, muscle, gill, intestine, and skin) of the fish hosts. There were significant differences in Cd, Cr, Cu, Fe, Mn, Zn, Hg, Mg, and Pb concentrations in tissues of fish and its par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 27 publications
4
21
0
Order By: Relevance
“…In the literature, Hysterothylacium aduncum has been reported from the Northeastern Atlantic [8,9], the Mediterranean Sea [10][11][12][13][14][15][16][17][18], the Black Sea [19], the Adriatic Sea [20], the Pacific and Atlantic waters of North America [21,22], Northwest Pacific, [23] and the Pacific Ocean costs of Japan [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, Hysterothylacium aduncum has been reported from the Northeastern Atlantic [8,9], the Mediterranean Sea [10][11][12][13][14][15][16][17][18], the Black Sea [19], the Adriatic Sea [20], the Pacific and Atlantic waters of North America [21,22], Northwest Pacific, [23] and the Pacific Ocean costs of Japan [24].…”
Section: Introductionmentioning
confidence: 99%
“…Acanthocephalans are presently recognized for their excellent metal accumulation capacities in both field and experimental conditions and adult cestodes as well as nematodes also seem to be promising bioindicators for some toxic elements (Eira et al 2009;Dural et al 2011). However, there is no data concerning adult trematodes parasites of fish.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown significantly higher quantity of heavy metal accumulation in tissues of endoparasites than their final hosts [8,9,91]. Among these is the higher concentration of lead and cadmium in Monobothrium wageneri and Bothriocephalus scorpil (cestodes) from the intestine of tench (Tinca tinca) and turbot (Scophthalmus maximus) than in the muscle, liver, and intestine of their fish host [3,4], and higher lead, cadmium, and cupper in Hysterothylacium aduncum (nematode) than its host sea bream (Sparus auratus) [91].…”
Section: Biological Indicators For Heavy Metal Contaminationsmentioning
confidence: 99%
“…Among these is the higher concentration of lead and cadmium in Monobothrium wageneri and Bothriocephalus scorpil (cestodes) from the intestine of tench (Tinca tinca) and turbot (Scophthalmus maximus) than in the muscle, liver, and intestine of their fish host [3,4], and higher lead, cadmium, and cupper in Hysterothylacium aduncum (nematode) than its host sea bream (Sparus auratus) [91]. Also, there were reports on an elevated selenium concentration in the cestode B. acheilognathi in comparison to the tissues of its fish definitive host [92].…”
Section: Biological Indicators For Heavy Metal Contaminationsmentioning
confidence: 99%